Mass gatherings medicine: public health issues arising from mass gathering religious and sporting events - Memish, Ziad A; Steffen, Robert; White, Paul; Dar, Osman; Azhar, Esam I; Sharma, Avinash; Zumla, Alimuddin (The Lancet (British edition), 2019)
Mass gathering events are associated with major public health challenges. The 2014 Lancet Series on the new discipline of mass gatherings medicine was launched at the World Health Assembly of Ministers of Health in Geneva in May, 2014. The Series covered the planning and surveillance systems used to monitor public health risks, public health threats, and experiences of health-care providers from mass gathering events in 2012 and 2013. This follow-up Review focuses on the main public health issues arising from planned mass gathering events held between 2013 and 2018. We highlight public health and research data on transmission of infectious diseases and antibiotic-resistant bacteria, mass casualty incidents, and non-communicable diseases, including thermal disorders. In the events discussed in this Review, the combination of a large influx of people, many from countries with outbreak-prone infectious diseases, with a high degree of crowd interactions imposed substantial burdens on host countries' health systems. The detection and transmission of antibiotic-resistant bacteria in pilgrims attending the Kumbh Mela and the Hajj raise concern of possible globalisation from mass-gathering religious events. Priorities for further investments and opportunities for research into prevention, surveillance, and management of these public health issues are discussed.